Application of Numbered Head Together (NHT) Cooperative Learning Model in Hindu Religious Education Lessons for Elementary School Students - Pradnyadewi, Ni Luh Putu; Suyanta, I Wayan (Jayapangus Press, 2024)
The right learning model can create a fun learning environment and make it easier for students to learn lessons. In the process of learning the conventional learning model, the lecture method used is less flexible and seems stiff. The ability to cooperate is useful for training students to accept that there are many differences with other friends with different backgrounds. The Numbered Head Together (NHT) cooperative learning model can maximize educators’ role in paying attention to students, and positive interactions occur between students and educators and students with other friends. This study aimed to obtain an innovative learning model. The data collection methods used were observation, interviews, document studies, and literature studies which were analyzed using qualitative descriptive analysis methods. The results showed that the application of the NHT cooperative learning model consisted of planning activities, implementation activities, final activities, and construction, resulting in increased interaction and discipline in learning, increased understanding in learning, and increased socialization and cooperation. Thus, it can be concluded that the application of the Numbered Head Together (NHT) cooperative learning model prioritized the role of students to be active by inviting students to learn while playing. The NHT learning model helped the learning process to be effective and efficient. The selection of the application of the Numbered Head Together (NHT) cooperative learning model in Hindu Religious Education lessons is expected that learning can give more impressions and deep meaning to students in learning with a group system.